Alternations of the gut microbiota and the Firmicutes/Bacteroidetes ratio after biologic treatment in inflammatory bowel disease - Yu-Chieh Tsai; Wei-Chen Tai; Chih-Ming Liang; Cheng-Kun Wu; Ming-Chao Tsai; Wan-Hsiang Hu; Pao-Yuan Huang; Chien-Hung Chen; Yuan-Hung Kuo; Chih-Chien Yao; Seng-Kee Chuah (Journal of Microbiology, Immunology and Infection)
Background: The inflammatory bowel disease (IBD), comprising Crohn's disease (CD) and ulcerative colitis (UC) is a complex disease with multifactorial etiology. The intestinal dysbiosis have been investigated to play an important role in IBD pathogenesis and disease activity. The aim of our study was to analyze the intestinal microbiota composition in IBD across different severity levels and the impact of biologic therapy on microbiota modulation. Methods: In this study, 27 IBD patients were recruited, including 14 patients undergoing biologic therapy for moderate to severe disease activity and 13 controls with inactive disease. The gut microbial composition was determined by 16 S ribosomal RNA gene sequencing of stool samples. Results: Biologic therapy led to significant clinical improvement in IBD disease activity after 48 weeks. About species richness, community alpha diversity was significant lower in active CD patients and enriched gradually after biologic therapy. The beta-diversity regard to the difference of bacterial community composition showed significant difference between patients in biologic and control group. A decrease in Firmicutes and increase in Bacteroidetes abundance were observed in patients with active disease, both in CD and UC. Biologic treatment induced shifts in gut microbiota, with increased Firmicutes and decreased Bacteroidetes, as well as improved F/B ratio gradually after treatment, correlating with disease activity. Conclusions: Our study suggested that gut microbiota differences changed after biologic therapies among IBD with different disease activity, and a rising Firmicutes/Bacteroidetes ratio could be a potential predictor for disease activity and treatment response monitoring.